2018
DOI: 10.1002/jcb.26880
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: miR‐200c, a tumor suppressor that modulate the expression of cancer stem cells markers and epithelial‐mesenchymal transition in colorectal cancer

Abstract: Colorectal cancer (CRC) is the most frequently diagnosed cancer and the most common gastrointestinal cancer worldwide. Due to the presence of populations of cancer stem cells (CSCs) that cause recurrence, the possibility of cancer treatment is very low. The aim of current study was to evaluate the inhibitory role of miR-200c on EMT, CSCs markers and β-catenin in HCT-116 and SW48 cell lines. The expression of miR-200c, EMT-related genes, CSCs markers, and β-catenin were quantified by qRT-PCR. Further, expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 99%
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 99%
“…As EZH2 determines HCC progression and metastasis, we next sought to investigate its role in miR-200c mediated tumorigenesis. It has been reported that miR-200c was a tumor suppressor microRNA in many cancers, such as colorectal cancer, renal cell carcinoma 27,28 . However, the in vivo role of miR-200c in HCC tumor cell growth has yet to be elucidated.…”
Section: Silencing Mir-200c Rescues the Sphere Formation And Migratiomentioning
confidence: 99%
“…Hence, miRNAs identification in cancer tissues and body fluids potentially have great clinical utility in early diagnosis and prognosis. However, the translation of miRNA-based knowledge to clinical practice in the treatment of CRC has not yet been achieved, and the impact of miRNAs on stem cell and colorectal CSC biology has emerged only recently [23][24][25][26][27][28][29]. Moreover, many reports in the scientific literature have been either in vitro or patientbased studies, and there are few studies aimed to identify colorectal CSC-associated miRNAs and their usefulness as tissue and/or serum biomarker in CRC patients.…”
Section: Introductionmentioning
confidence: 99%